PENGARUH STORE ATMOSPHERE DAN BRAND IMAGE TERHADAP KEPUASAN PELANGGAN PADA LILS BEAUTY STUDIO LEBAK BULUS KOTA JAKARTA SELATAN - SETIANA, ANA (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The purpose of this study was to determine the effect of Store Atmosphere and Brand Image on Customer Satisfaction at Lils Beauty Studio Lebak Bulus, South Jakarta City. The method used is quantitative. The sampling technique uses the Slovin formula and obtained a sample of 89 respondents. In collecting data, researchers used a questionnaire. Data processing used the SPSS version 27 application. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of the study showed that Store Atmosphere has a significant effect on Customer Satisfaction with a determination coefficient value of 70.9% and the hypothesis test obtained the results of t count > t table or (14.551 > 1.988). Brand Image has a significant effect on Customer Satisfaction with a determination coefficient value of 84.7% and the hypothesis test obtained the results of t count > t table or (21.933 > 1.988). Store Atmosphere and Brand Image have a significant effect simultaneously on customer satisfaction with the regression equation Y = 0.902 + 0.191X1 + 0.796X2. The coefficient of determination value is 85.4% and the hypothesis test obtained the results of F value > F table value, or (252.027 > 2.710). Keywords: Store Atmosphere; Brand Image; Customer Satisfaction